2007
DOI: 10.1108/17468800710718903
|View full text |Cite
|
Sign up to set email alerts
|

Is performance management applicable in developing countries?

Abstract: Purpose -To test whether performance management is a useful management tool for organisations in developing countries. Design/methodology/approach -Firstly, an overview is given of the status of performance management in developing countries and in particular in Africa. Secondly, prescriptive empirical research, in the shape of a case study at the Tanzanian College of Business Education, is used to test whether performance management is a useful technique for organisations in developing countries. Findings -It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 16 publications
2
73
0
Order By: Relevance
“…It is shown that only 5 per cent of studies have tried to test institutional theory empirically in developing countries [10]. De Wall [11] stated that performance management is one of the institutional theories "whose validity needs to be tested in an emerging country's context, as this context can be more dynamic and be completely different from a developed country's context". Moreover, it is found in the literature review that most studies on performance management and employee job satisfaction are performed in industries that have less complex technologies.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that only 5 per cent of studies have tried to test institutional theory empirically in developing countries [10]. De Wall [11] stated that performance management is one of the institutional theories "whose validity needs to be tested in an emerging country's context, as this context can be more dynamic and be completely different from a developed country's context". Moreover, it is found in the literature review that most studies on performance management and employee job satisfaction are performed in industries that have less complex technologies.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the problems of PM identified by the interviewees. Several prior studies found that if there is no link between the PMS and the evaluation and rewards system, organisational members will not be evaluated and rewarded for their good performance (De Waal, 2007;De Waal & Counet, 2008;Karuhanga, 2010). This situation might lead organisational members to consider issues regarding the PMS as not being very important.…”
Section: Discussionmentioning
confidence: 99%
“…Performance measurement refers to the use of financial and non-financial information by managers to make decisions pertaining to organisational activities with a focus on the pre-determined goals (De Waal 2007;Karuhanga, 2010). Therefore, performance measurement refers to the set of actions put in place to determine the extent to which an organisation is achieving its pre-determined targets (Amaratunga et al, 2001).…”
Section: Performance Measurement Systems -Conceptualizationmentioning
confidence: 99%
See 2 more Smart Citations